2016
DOI: 10.1007/s00223-016-0162-2
|View full text |Cite
|
Sign up to set email alerts
|

Adipose, Bone, and Myeloma: Contributions from the Microenvironment

Abstract: Researchers globally are working towards finding a cure for multiple myeloma (MM), a destructive blood cancer diagnosed yearly in ~750,000 people worldwide [1]. Although MM targets multiple organ systems, it is the devastating skeletal destruction experienced by over 90% of patients that often most severely impacts patient morbidity, pain, and quality of life. Preventing bone disease is therefore a priority in MM treatment, and understanding how and why myeloma cells target the bone marrow (BM) is fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 115 publications
(148 reference statements)
0
36
1
Order By: Relevance
“…Although the more predominant white adipose tissue partakes in energy storage, insulation, mechanical support for internal organs, and endocrine and immune modulation, brown adipocytes have extensive thermogenic properties . Bone marrow adipose tissue residing on the endosteal surface and throughout the bone marrow cavities has a complex set of regulatory functions directly impacting the osteogenic, angiogenic, and immunogenic properties of the bone marrow niche . Increased marrow adiposity can have multiple effects on the marrow and bone because adipocytes express and secrete multiple factors, such as adepsin, leptin, adiponectin, TNF, and angiotensinogen with significant pleiotropic effects on the local microenvironment of bone marrow cells.…”
Section: Impact Of Obesity and High‐fat Diet On Mmbdmentioning
confidence: 99%
“…Although the more predominant white adipose tissue partakes in energy storage, insulation, mechanical support for internal organs, and endocrine and immune modulation, brown adipocytes have extensive thermogenic properties . Bone marrow adipose tissue residing on the endosteal surface and throughout the bone marrow cavities has a complex set of regulatory functions directly impacting the osteogenic, angiogenic, and immunogenic properties of the bone marrow niche . Increased marrow adiposity can have multiple effects on the marrow and bone because adipocytes express and secrete multiple factors, such as adepsin, leptin, adiponectin, TNF, and angiotensinogen with significant pleiotropic effects on the local microenvironment of bone marrow cells.…”
Section: Impact Of Obesity and High‐fat Diet On Mmbdmentioning
confidence: 99%
“…BMAT volume increases with age and occupies a significant portion of the BM, as well as composing over 10% of the average person's total adipose tissue mass [21]. Of significance to this review is the finding that elevated regulated BMAT volume, which is located in close proximity to the trabecular bone and hematopoietic elements and increases with age, is directly correlated with bone loss and resultant osteoporosis [22]. A mutually incompatible relationship arises between adipose components of the BM and bone-forming components, as osteoblastogenesis and the factors that support it often inhibit adipogenesis, and vice versa.…”
Section: Bone Marrow Adipose Tissuementioning
confidence: 99%
“…A handful of studies in myeloma have found that MAT produces factors that support myeloma disease progression, although certain adipokines, such as adiponectin [16], have been found to inhibit myeloma, confounding the roles of MAT in myeloma [17,18]. Cell-derived factors (molecules, lipids, small metabolites, or microRNAs) may be free or embedded in exosomes or other microvesicles and transferred between BMAs and myeloma cells as one method of communication [19].…”
Section: Mat Adipokines Lipids and Cell-cell Contact Supports Camentioning
confidence: 99%